Birth Outcomes of Infants Born to Mothers with Alopecia Areata: A Nationwide Population-based Study in Korea - Jung-Won Shin; Taeuk Kang; Heather Swan; Kyungho Paik; Chang-Hun Huh; Hyun Jung Kim (Acta Dermato-Venereologica)
Data on pregnancy outcomes in patients with alopecia areata (AA) are limited. The aim of this study is to determine the association between maternal AA and risk of adverse birth outcomes in children. A retrospective cohort study was conducted on 45,328 children born to mothers with AA and 4,703,253 controls born to mothers without AA using the Korean National Health Insurance Claims database from 2002 to 2016. Multivariate logistic regression analyses were performed to evaluate the association between maternal AA and the birth outcomes of their children. Infants born to mothers with AA exhibited a significantly higher risk of preterm birth (odds ratio [OR] 1.39, 95% CI 1.33–1.45; adjusted OR [aOR] 1.07, 95% CI 1.01–1.13), low birthweight (OR 1.36, 95% CI 1.30–1.42; aOR 1.11, 95% CI 1.05–1.17), and Caesarean section birth (OR 1.24, 95% CI 1.22–1.26; aOR 1.12, 95% CI 1.08–1.15) than controls. In addition, the risk of congenital malformations was also significantly higher in infants born to mothers with AA (OR 1.19, 95% CI 1.15–1.22; aOR 1.10, 95% CI 1.07–1.14), especially for malformations of the urinary (OR 1.33, 95% CI 1.19–1.48; aOR 1.16, 95% CI 1.04–1.29) and musculoskeletal (OR 1.19, 95% CI 1.12–1.27; aOR 1.12, 95% CI 1.05–1.19) systems, than controls. Maternal AA is associated with an increased risk of adverse birth outcomes in infants.